Assessment of the influence of gluten quality on highland barley dough sheet quality by different instruments. Issue 2 (23rd February 2022) - Wang, Tianxiu; Jiang, Yiyi; Liu, Shuyi; Obadi, Mohammed; Xu, Bin; Jiang, Song
Abstract: This study was to compare the results of texture analyzer with those of farinograph and extensograph and determine whether texture analyzer could be used to evaluate the processing quality of highland barley flour (HBF) dough sheet. The farinograph and extensograph tests were used to determine the reconstituted flour properties, a texture analyzer was applied to measure the tensile strength (TS) of HBF dough sheet, and the content of glutenin macropolymer (GMP), free sulfhydryl (‐SH) and secondary structure of protein and microstructure in HBF dough sheet were investigated. Furthermore, correlations between these parameters were determined by regression analysis and Pearson correlation coefficient. It was suggested that the reconstituted flours with a higher gluten index showed a higher farinograph quality number (FQN) and greater maximum resistance to extension ( R m ). HBF dough sheets with higher gluten index possessed higher GMP and lower free ‐SH contents, a more ordered secondary structure of protein, resulting in a more compact gluten network and a stronger TS. The regression and correlation analysis showed that TS was positively correlated with FQN and R m . In addition, it was significantly correlated with the content of GMP, ‐SH, secondary structure of protein and gluten network. It was concluded that texture analyzer could be an alternative approach to evaluate the processing quality of HBF dough sheet. Moreover, the gluten index of flours could be used to predict the processing quality of HBF dough sheet.